Electron transport bilayer with cascade energy alignment based on Nb2O5–Ti3C2 MXene/TiO2 for efficient perovskite solar cells. Issue 10 (23rd February 2023) - Lemos, Hugo G.; Rossato, Jessica H. H.; Ramos, Roberto A.; Lima, João V. M.; Affonço, Lucas J.; Trofimov, Sergei; Michel, Jose J. I.; Fernandes, Silvia L.; Naydenov, Boris; Graeff, Carlos F. O.
Abstract : Nb2 O5 –Ti3 C2 exhibits beneficial band-edge alignment, favoring carrier migration with a higher density of extracted charges and increased electron lifetime. Abstract : Nb2 O5 shows promising features for electron transport layers (ETL) in perovskite solar cells (PSCs), such as suitable band alignment and ultraviolet stability. Here, we studied the incorporation of Ti3 C2 T x MXene in a solution-processable compact layer as a component of ETLs for PSCs. The addition of 0.4 wt% MXene with respect to niobium ethoxide was shown to enhance the PCE (19.46% for the champion device) and stability (96% of its original PCE after 500 hours) compared to pristine devices. The improved performance of the Nb2 O5 –Ti3 C2 devices (0.4 wt%) could be attributed to the adapted alignment of the energy band between perovskite and ETL layers, which favors electron transport and extraction. In addition, the high electrical conductivity of MXenes worked as a free pathway for the extracted electrons preventing charge recombination. These features were corroborated by Photo-CELIV, which showed a higher density of extracted charges and increased charge carrier lifetime for Nb2 O5 –Ti3 C2 based devices. Hence, the results unveiled in this work indicate that MXenes are promising 2D materials for tuning Nb2 O5 based ETLs. Future works shall focus on other MXene compounds to further boost PSC performance and stability.